Gut flora shift caused by time-restricted feeding might protect the host from metabolic syndrome, inflammatory bowel disease and colorectal cancer - Hu, Dandan; Mao, Yilei; Xu, Gang; Liao, Wenjun; Yang, Huayu; Zhang, Hongbing (Translational Cancer Research, 2018)
Background: Time-restricted feeding (TRF) allows for 8–10 hours of feeding each day, and has been reported to have favorable health outcomes. With the close relationship between diet and gut microbiome in mind, we investigated how microflora adapt to TRF, and the possible impact of this adaptation on metabolic and digestive diseases. Methods: We randomly assigned 40, 9-week-old, wild-type Kunming mice into 4 feeding regimens. Group A was treated with TRF for 2 months, group B had ad libitum (AD) access to food in the first month before TRF in the second, group C went through TRF in the first month but resumed AD pattern in the second month, and group D had continuous AD access to food. Results: Health promoting micro groups including Firmicutes phylum, Clostridia class, Ruminococcaceae family, and Roseburia genus, etc. were increased by TRF, while those detrimental groups were inhibited. Conclusions: Changes in the gut microflora caused by TRF suggest possible protective effects against obesity, disruption of blood glucose homeostasis, and bowel diseases.